Numerical Solution Of The Goursat Problem. - Md. Ismail, Ahmad Izani; Nasir, Mohd. Agos Salim; Talib, Abdullah Zawawi (2004)
The Goursat problem, associated with hyperbolic partial differential equations, arises in several areas of applications. Several finite difference schemes have been proposed to solve the Goursat problem.